Caracterización de los pellets con fines bioenergéticos elaborados a partir de la madera de cuatro fabáceas - Hernández Méndez, Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2025)
This research evaluated the characteristics of pellets from four Fabaceae species: Acacia farnesiana (L.) Willd, A. pennatula (Schl. et Cham) Benth, Albizia plurijuga (Standl.) Britton & Rose, and Prosopis laevigata (Humb. & Bonpl.) Johnst. These were compared with Pinus spp. pellets for their bioenergetic use. The following analyses were conducted: particle size distribution (granulometry), proximate analysis (including moisture content, ash, volatile matter, and fixed carbon), elemental composition (C, H, O, N, S), mineral analysis in ashes, higher heating value, length and diameter measurements, individual density, bulk density, and mechanical durability. The highest concentration of particles in the granulometry was found in the 1.0, 0.5-, and 2-mm fractions. In the proximate evaluation, the Fabaceae showed a higher content of ash and fixed carbon, in contrast to a lower content of volatile matter, compared to Pinus spp. All species met the moisture standards. The elemental composition of the pellets was determined, revealing differences in the proportions of C, H, N, and O. Additionally, 22 elements were identified in the mineral analysis of the ashes, including Al, Ca, Fe, K, Mg, Mn, Na, P, and Si. Pine pellets exhibited the highest heating value, although all pellet types exceeded the limits established by the standards. The pellets complied with dimensional and density standards. Pinus spp. demonstrated greater mechanical durability than the Fabaceae. According to the results obtained, Fabaceae are viable for pellet production, albeit with lower durability than Pinus spp.

La presente investigación evaluó las características de pellets para cuatro especies de Fabaceae: Acacia farnesiana (L.) Willd, A. pennatula (Schl. et Cham) Benth, Albizia plurijuga (Standl.) Britton & Rose y Prosopis laevigata (Humb. & Bonpl.) Johnst., y se compararon con pellets de Pinus spp., para su uso bioenergético. Se realizaron los análisis: granulometría, análisis proximal que incluye la medición de la humedad, la materia inorgánica, materia volátil y el carbono fijo. Composición elemental: C, H, O, N, S. Análisis de minerales en cenizas, valor calorífico superior, mediciones de longitud y diámetro, densidad individual, densidad volumétrica y durabilidad mecánica. La mayor concentración de partículas en la granulometría se encontró en las fracciones de 1.0, 0.5 y 2 mm. En la evaluación proximal, las Fabaceae mostraron mayor contenido de materia inorgánica y carbono fijo, en contraste, menor contenido de materia volátil, en comparación con Pinus spp. Todas las especies cumplieron con los estándares de humedad. Se determinó la composición elemental de los pellets, con diferencias en las proporciones de C, H, N y O. Por otro lado, se identificaron 22 elementos en el análisis de minerales en las cenizas Al, Ca, Fe, K, Mg, Mn, Na, P y Si. El pino mostró el mayor valor calorífico, aunque todos los tipos de pellets superaron los límites establecidos por las normas. Los pellets cumplieron con las normas de dimensiones y densidad. Pinus spp. mostró mayor durabilidad mecánica que las Fabaceae. De acuerdo con los resultados obtenidos, las Fabaceae son viables para elaborar pellets, aunque con menor durabilidad que Pinus spp.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2025-1204; Bioenergía; Granulometría; Durabilidad mecánica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19367